(untitled) (Kathmandu University Medical Journal, 2022)
Background Pneumothorax is a condition in which air or other gas is present in the pleural cavity. Mainstay of management of pneumothorax is to remove the air from the pleural space usually done by chest tube insertion. There is still uncertainty whether minimal invasive management with pigtail catheter is sufficient for the management of pneumothorax. Objective To find the effectiveness, safety, tolerability, efficacy of pigtail catheters and large bore chest tubes. Method Prospective comparative study was done in Dhulikhel Hospital between August 2019 till August 2021. Chest tube insertion used to be the only available treatment modality till December 2020 (15 months). Following January 2021 after obtaining ethical clearance for use of pigtail insertion for pneumothorax, this treatment modality was done (8 months). Result Among 76 patients, 52(68.4%) underwent a large bore chest tube and 24 (34.6%) pigtail catheter patients. Mean age of the patients was 48 years (SD 18.01). Duration of hospital stay and length of hospital stay was more in large bore catheters and less in pigtail catheters. Eight hours post tube placement of the expansion of the lungs was present in pigtail and was statistically significant. Pain killer used in pigtail catheters was limited to Non-steroidal anti-inflammatory drugs, for large bore catheter opioids were added and were statistically significant. Conclusion Pigtail catheter is nearly effective as compared to traditional wide bore catheters.